Controlled synthesis of aligned Bi2S3 nanowires, sharp apex nanowires and nanobelts with its morphology dependent field emission investigations - Warule, Sambhaji S.; Chaudhari, Nilima S.; Kale, Bharat B.; Pandiraj, S.; Khare, Ruchita T.; More, Mahendra A. (Crystengcomm, 2013)
Well-aligned ultra-long Bi2S3 nanowire arrays with three kinds of apex morphology - abruptly sharpened apex, thin belt and flat - have been systematically fabricated on tungsten (W) foil by a facile hydrothermal method. The structural and morphological studies reveal formation of distinct tip morphologies, possessing high aspect ratio, single crystalline nature and growth along the orthorhombic [001] axis. A plausible growth mechanism has been proposed on the basis of observed experimental results. The field emission properties of Bi2S3 nanowires and sharp apex Bi2S3 nanowires are investigated. From the field emission studies, the values of the turn-on field, required to draw emission current density of similar to 0.1 mu A cm(-2), are observed to be similar to 2.01 and 1.21 V mu m(-1) for nanowires and sharp apex nanowires, respectively. Furthermore, ultra-long Bi2S3 nanowires are also grown on the W microtip (brush-like) from which very high emission current density similar to 11 mA cm(-2) has been drawn. These results are helpful for the design, fabrication and optimization of integrated field emitters using 1D nanostructures as cold cathode material.